Peningkatan Hasil Belajar Siswa Kelas VI dengan Penerapan Experiental Learning pada Mata Pelajaran IPA Materi Sistem Tata Surya - Dwi Rismawati Ningrum; Novita Erliana Sari; Sari Kustiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to enhance the learning outcomes of sixth-grade students in the subject of Science by implementing the Experiential Learning method on the topic of the solar system. The research methodology used in this study is Classroom Action Research (CAR) with an Experiential Learning instructional design. The research participants consisted of 23 sixth-grade students from SDN Oro-Oro Ombo, and the research instrument used was an observation sheet to measure students' learning achievements. The research procedure consisted of the pre-cycle phase, cycle one, and cycle two. In the pre-cycle phase, an initial evaluation in the form of a pre-test was conducted to measure students' understanding before implementing the Experiential Learning method. Subsequently, in cycle one and cycle two, evaluations were conducted in the form of post-tests to measure the extent of students' comprehension after participating in the Experiential Learning-based instruction. The research results showed that in the pre-cycle phase, there were 4 students (17%) who achieved the proficiency level. This number increased to 9 students (39%) in cycle one, and there was a further improvement in cycle two, with 18 students (78%) reaching the proficiency level and meeting the criteria. Therefore, it can be concluded that the implementation of Experiential Learning in teaching the solar system significantly improves the learning outcomes of students in the Science subject. The students demonstrated an increased understanding of concepts, information retention, and scientific thinking skills. Additionally, this method also enhances students' interest, motivation, and practical problem-solving skills. Therefore, it is recommended for teachers and educational institutions to consider using the Experiential Learning method as an engaging alternative in the teaching and learning process to achieve better learning outcomes in the Science subject, especially in the topic of the solar system. Keywords: Experiential Learning, Learning Outcomes, Solar System.